Monarchianism and Origen's Early Trinitarian Theology - Waers, Stephen (Vigiliae Christianae, Supplements, 2022)
This book argues that Origen's early Trinitarian theology cannot be understood apart from his engagement with monarchianism. After providing a detailed, synthetic account of monarchianism in the early third century, the book considers Origen's response to monarchianism alongside the responses of his rough contemporaries. Specifically, the final chapters address the question of Origen's subordinationism. When viewed in his contemporary context and not through the anachronistic lens of Nicene theology, this study argues that Origen's so-called subordinationism was an intentional anti-monarchian polemic strategy.